Enhancement of Visuospatial Working Memory by the Differential Outcomes Procedure in Mild Cognitive Impairment and Alzheimer’s Disease - Vivas, Ana B.; Ypsilanti, Antonia; Ladas, Aristea I.; Kounti, Foteini; Tsolaki, Magda; Estévez, Angeles F. (Frontiers in Aging Neuroscience, 2018)
In the present study we investigated the efficacy of the differential outcome procedure (DOP) to improve visuospatial working memory in patients with Alzheimer’s disease and Mild Cognitive Impairment (MCI). The DOP associates correct responses to the to-be-remember stimulus with unique outcomes. Eleven patients diagnosed with Alzheimer’s disease, 11 participants with MCI, and 17 healthy matched controls performed a spatial delayed memory task under the DOP and a control condition (non-differential outcomes –NOP-). We found that performance (terminal accuracy) was significantly better in the DOP condition relative to the NOP condition in all three groups of participants. AD patients performed worse, and took longer to benefit from the DOP. In line with previous animal and human research, we propose that the DOP activates brain structures and cognitive mechanisms that are less affected by healthy and pathological aging, optimizing in this way the function of the cognitive system.